Redefining the Concept of Sabilillah to Strengthen Arguments for Gender-Just Zakat Distribution for Vulnerable Minority Groups (Women and Children Victims of Violence) - Choironi, Ulfa; Fajriyah, Iklilah Muzayyanah Dini (Borong Newinera Publisher, 2026)
Studies on zakat distribution from a gender justice perspective have grown significantly. Zakat should not be understood only as a relationship between muzakki and mustahik in general, but also as a means of showing support for vulnerable groups, especially women and children who are victims of violence. In this sense, zakat can function as an instrument for promoting justice in the social order. This study uses a literature-based approach to examine patterns in previous research. The findings show that zakat distribution in Indonesia has not yet been optimally directed toward women and children who experience violence. Even so, the literature reveals important opportunities for developing a more inclusive and gender-responsive model of zakat management. A number of previous studies have shown concern for marginalized groups and opened space for a broader interpretation of zakat distribution. The study also finds that one of the main weaknesses of zakat institutions in Indonesia is the limited application of inclusive and gender-responsive approaches in addressing complex social realities. Therefore, a more critical and gender-fair perspective is needed, especially in reinterpreting the eight categories of zakat recipients in a more inclusive way. Such an approach is important for creating a more equitable welfare system for society. Further empirical research is needed to strengthen these findings, expand collaboration, and ensure that zakat distribution can have a real impact on vulnerable minority groups, particularly women and children who are victims of violence.